Elite universities, fields of study and top salaries: Which degree will make you rich?. (11th August 2018) - Sullivan, Alice; Parsons, Samantha; Green, Francis; Wiggins, Richard D.; Ploubidis, George
Abstract : This article assesses the chances of entering the top 5% of earners for a British cohort currently in their 40s. We assess the difference made by a university degree from an elite (Russell Group) or non‐elite university, and from different undergraduate fields of study. Our study uses rich longitudinal data from the 1970 British Cohort Study (BCS70). This allows us to control for an unusually large range of potential confounding factors, including childhood socio‐economic circumstances, cognitive scores, secondary schooling and prior qualifications. We find that large raw differences in the chances of achieving a top salary are strongly attenuated by our controls, but substantial differences between degree subject areas remain. The large gap between men and women in the chance of gaining a top salary is not explained by the type of degree achieved, and we found no evidence of gender differences in the gains from institutional prestige or particular fields of study.